Consumption and impact of ultra-processed food products on the nutritional profile of Uruguayan schoolchildren (Archives of Pediatrics of Uruguay, 2021)
Goals: estimate the caloric and nutritional intake associated with non-communicable diseases, according to the level of food processing in schoolchildren aged 4 to 12 in the city of Montevideo.Method: cross-sectional study based on 24-hour reminders carried out in 21 public schools with a school canteen service in the city of Montevideo in 2018, within the framework of the national evaluation of the School Food Program of the National Public Education Administration. With this purpose, the children’s diet source was analyzed in terms of caloric intake, total fat, saturated fat, sodium, potassium, dietary fiber and free sugars. We used PC SIDE software to estimate the distribution of nutrient intake and adjust for interindividual and intraindividual variances.Results: on average, caloric adequacy reached 113% of the group’s requirement and 54% of schoolchildren consume calories excessively. 28% of the calories come from Ultra-Processed Products (UPP) and 18.9% come from free sugars, equivalent to practically 100 grams of daily consumption. UPP consumption was found in practically all the schoolchildren studied and was associated with a more unfavorable dietary profile, which increases intake does. Conclusions: these findings enable us to state that the consumption of UPP is generalized, starts at an early age and that its higher consumption is associated with an unfavorable dietary profile.Conclusions: these findings enable us to state that the consumption of UPP is generalized, starts at an early age and that its higher consumption is associated with an unfavorable dietary profile.
Keywords: Food; Child nutrition; Diet, food and nutrition; Child